Comparing the eating out experiences of consumers seeking to avoid different food allergens - Julie Barnett; Fiona M. Begen; M. Hazel Gowland; Jane S. Lucas (BMC, 2018)
Abstract Background Eating outside the home is challenging for consumers with food allergy (FA) and intolerance (FI) and lack of allergen information provision in eating out venues can lead to unnecessary restrictions. Following European legislation (2014) designed to improve allergen information provision, little is known about differences in information provision experienced by consumers seeking to avoid particular allergens, or how this impacts on their eating out experiences. This study compared the information provision that consumers with FA/FI to different allergens experience when eating out. Methods Using mixed methods, participants were recruited from across the UK and took part in self-report surveys or in-depth interviews. Surveys were completed by 232 participants avoiding either gluten (n = 66), nuts (peanuts/tree nuts) (n = 94), or milk (n = 74), and responses were subject to quantitative analyses. Interviews were carried out with 49 participants avoiding either gluten (n = 13), nuts (n = 14), milk (n = 13) or a combination of these allergens (n = 9), and analysed using the framework approach. Results Although general improvements in information provision following the legislation were reported, variations in provision between allergen groups led participants seeking to avoid milk to conclude that their dietary needs were less well-understood and seen as less important. These perceptions were reflected in a reluctance to involve eating out venue staff in deliberations about the potential for milk-free meal options. Conclusions The provision of visual indicators of the presence of milk and of staff trained in allergen-awareness would improve the eating out experiences of consumers seeking to avoid milk. Medical professions can play a key role in encouraging these patients to pursue their right to make enquiries about allergens in order to avoid accidental milk ingestion when eating out.